Effect of Principals’ Emotional Intelligence on Schools’ Academic Performance: A Survey of Nepali Institutional Schools - Khadka, Jiban (Education and Development, 2019)
Emotional intelligence (EI) has become a central concern to carry out any study on leadership and its effectiveness in schools and other institutions. This study was intended to investigate the effect of the principals’ EI on the academic performance of Nepali institutional schools. A sample of 121 principals and 491 teachers from the schools of three districts of Nepal (Jhapa, Kathmandu and Kaski) was drawn following cluster sampling method. The data were collected through Emotional Intelligence Survey Questionnaire. From the data analysis using non-parametric statistical measures, it was revealed that the principals had higher level of emotional intelligence irrespective of their demographic characteristics. The findings indicated that the schools’ principals were emotionally intelligent and effective in maintaining the schools’ academic performance. The findings can lead to conclude that leadership performance can be enhanced in schools by developing emotional intelligence in the principals’ leadership behaviour.